Management of septic arthritis: a systematic review. Issue 4 (12th January 2007) - Mathews, C J; Kingsley, G; Field, M; Jones, A; Weston, V C; Phillips, M; Walker, D; Coakley, G
Abstract : Objective: To evaluate the existing evidence on the diagnosis and management of septic arthritis in native joints. Design: Systematic review. Data sources: Cochrane Library, Medline, Embase, National Electronic Library for Health, reference lists, national experts. Review methods: Systematic review of the literature with evaluation of the methodological quality of the selected papers using defined criteria set out by the Clinical Effectiveness and Evaluation Unit of the Royal College of Physicians. Results: 3291 citations were initially identified. Of these, 189 full text articles were identified for potential selection. Following review of these full text articles, 80 articles were found to fulfil the inclusion criteria and were included in the final list. Conclusions were drawn on the diagnosis, investigation and management of septic arthritis. Discussion: Little good quality evidence exists to guide the diagnosis and management of septic arthritis. Overall, no investigation is more reliable in the diagnosis of septic arthritis than the opinion of an experienced doctor. Aspiration and culture of synovial fluid is crucial to the diagnosis, but measurement of cell count is unhelpful. Antibiotics are clearly required for a prolonged period, but there are no data to indicate by which route or for how long. Key unanswered questions remain surrounding the medical and surgical management of the infected joint.